Sishen Wan® Ameliorated Trinitrobenzene-Sulfonic-Acid-Induced Chronic Colitis via NEMO/NLK Signaling Pathway - Wang, Hai-Yan; Zhao, Hai-Mei; Wang, Yao; Liu, Yi; Lu, Xiu-Yun; Liu, Xue-Ke; Chen, Fang; Ge, Wei; Zuo, Zheng-Yun; Liu, Duan-Yong (Frontiers in Pharmacology, 2019)
The nuclear factor (NF)-κB signaling pathway plays an important role in the initialization and development phase of inflammatory injuries, including inflammatory bowel disease (IBD). Sishen Wan (SSW) is a classic Chinese patent medicine listed in the Chinese Pharmacopeia, which is usually used to treat chronic colitis; however, it is unclear whether SSW can treat IBD via the NF-κB signaling pathway. In the present study, the therapeutic effect of SSW was demonstrated by the decreased index of colonic weight, macroscopic and microscopic score, and pathological observation in chronic colitis induced by trinitrobenzene sulfonic acid. In colonic mucosa of rats with chronic colitis, SSW reduced the levels of calprotectin and eliminated oxidative lesions; downregulated expression of interferon-γ, interleukin (IL)-1β and IL-17; increased expression of IL-4; and suppressed expression of NF-κB p65 and NF-κB essential modulator (NEMO)-like kinase (NLK). Furthermore, SSW inhibited ubiquitinated NEMO, ubiquitin-activated enzyme, and E2i activation, and phosphorylation of downstream proteins (cylindromatosis protein, transforming growth factor-β activated kinase and P38). These results show that the therapeutic effects of SSW in chronic colitis were mediated by inhibiting the NEMO/NLK signaling pathway to suppress NF-κB activation.